Terminologien und Ordnungssysteme in der Medizin Standortbestimmung und Handlungsbedarf in den deutschsprachigen Ländern - Rienhoff, Otto; Semler, Sebastian C. (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2015)
"The field of international medical terminology is complex. In the first part of the book, recommendations are published in which the experts involved advocate the use of internationally used terminologies (e.g. LOINC, SNOMED CT) to ensure an international exchange of information. Here it becomes particularly clear that detailed solutions can only be gradually approached and that a national strategy is urgently required. In the second part, experts from science, associations and industry provide the most important technical background information on individual topics and terminology systems, e.g. on ICD-11, SNOMED CT, LOINC and identifiers in the pharmaceutical sector, on terminology servers and semantic management, metadata, acceptance factors and definitions as well as future ones Importance of terminology systems in research and care."